From Dada to the Browser: Internet Art and the Democratization of Artistic Production in the Digital Era. - Ryan, John (International Journal of Critical Cultural Studies, 2014)
"Internet artists" make use of emerging digital platforms, but also push the boundaries of technology itself. Although different factors contributed to its initial development, internet art has grown primarily through advances in interface technologies and computer programming. Yet internet art has not emerged in an art-historical vacuum. The influence of Dadaism, the Fluxus movement, conceptual art, participatory art, and pre-internet media-based works, such as Nam June Paik's Participation TV, are all evident in the works of contemporary internet artists. Through the "global village" of McLuhan, the "simulacra" of Baudrillard and the "relational aesthetics" of Bourriaud, I argue that the internet and related digital media have contributed to the democratization of art. While exploring the effects of emerging technologies on internet art, I also consider the technological, artistic, and social developments that have been triggered by artists across different forms of digital media.